Relationship of vital problems with higher social conflictsity in veterans with PTSD and TBI according to modal analysis - Smashna Олена (Psychosomatic Medicine and General Practice, 2020)
Objective. Factors of the environment, society, as well as internal personal psychological factors and personal experience, affect the formation of mental disorders. Society and stressors determine which behavioral scenarios of the individual will be relevant. Personality characteristics through behavioral responses determine which of the many potential stressors are significant and what impact they will have on the individual. Modern understanding of the genesis of PTSD shows that the individual’s overcoming of traumatic stressors of the combat situation depends on three groups of factors: the nature of traumatic events, individual psychological characteristics of veterans, and the conditions in which the demobilized falls after returning from war. The interaction of these factors with the process of cognitive processing of psycho-traumatic experience leads to an increase in mental stress or to the gradual assimilation of psycho-traumatic experience. As a result, it is possible to expect mental "restabilization" or the emergence of PTSD. The presence of additional bio-psycho-social stressors (e.g., substance abuse, family instability, concomitant medical comorbidity) significantly increases the likelihood of developing PTSD in veterans and the degree of social maladaptation in PTSD. The comorbidity of PTSD and TBI further increases the likelihood of social maladaptation in demobilized servicemen. The relevance of studying the impact of life problems on social adaptation in veterans with PTSD and TBI is determined by the need to develop an adequate set of medical and psychological interventions and socio-psychological rehabilitation.Purpose: to investigate medical and anamnestic features and to conduct a modal analysis of life problems of veterans with PTSD and mTBI. Methods and materials. 329 combatants (members of the Armed Forces, the National Guard, and "volunteer battalions") in eastern Ukraine who suffered from PTSD and mTBI were examined.The socio-demographic and medical-anamnestic examination was performed using the Unified map of patient research developed by us. Modal analysis of existing problems was carried out on the basis of ICD-10, their presence was assessed by diagnostic headings: Z55 - Z73. Results. Antisocial traits and increased social conflict in veterans with PTSD and mTBI correlated with marital/sexual and parental problems, as well as insufficient family support, problematic alcohol/drug use, and inadequate social skills. and conflicting perceptions of their own social status. Conclusions. The negative factors influencing the course of PTSD and mTBI identified by us became the material for the formation of targets of psychosocial therapy and optimization of pharmacological treatment.